Design Optimization and Performance Evaluation of the Open-Graded Friction Course with Small Particle Size Aggregate - Hao Fu; Chaohui Wang; GongXin Yu; Qian Chen; Luqing Liu (Advances in Civil Engineering)
This study aims to optimize the bonding performance between the wearing course and the used pavement or the underlying layer and further improve the service quality and durability of the open-graded friction course with small particle size aggregate (ultrathin OGFC). The ultrathin OGFC including waterborne epoxy resin emulsified asphalt (WEA) bonding layer and open-graded asphalt concrete with 9.5 mm nominal maximum aggregate size gradation was optimized. The construction timing of the open-graded asphalt mixture was determined. The road performance, wear resistance, and interlaminar bonding durability of the ultrathin OGFC were comprehensively evaluated. The results show that, based on the basic properties of the open-graded asphalt mixture, its asphalt aggregate ratio is recommended to be 5.0–5.5%. Based on interlaminar shear strength, it is recommended that the open-graded asphalt mixture is paved immediately after WEA bonding material was sprayed, and the bonding layer does not spread aggregate. The WEA containing 20% waterborne epoxy resin (WER) is recommended as bonding layer for the ultrathin OGFC, and the optimized spraying amount is 1 kg/m2. The ultrathin OGFC has good antisliding, drainage, and wear resistance properties. The interlaminar bonding performance, water stability, and durability of WEA bonding layer are obviously better than those of high viscosity asphalt (HVA) and SBS-modified asphalt. The WEA bonding layer can better resist interlaminar shear failure and improve the service quality and service life of the ultrathin OGFC.